Pavlovo preseganje judovstva in helenizma v razumevanju telesa in svobode - Matjaž, Maksimilijan (Edinost in dialog, 2025)
Paul’s proclamation of the Gospel is radically new. This claim is supported by three key concepts developed in his letters: soteriology and the theology of the cross; salvation and new life through baptism in the Holy Spirit; and the concept of freedom in Christ – life in Him. Paul’s theology of freedom and of the body is not only ethical and normative, but also epistemological and ontological. Paul transforms the system of knowledge, as the knowledge of God is no longer grounded in rational speculation or the Law, but in participation in Christ. Yet Paul, as the apostle to the nations who spread the Gospel, also drew from Judaism, which influenced his theological perspective, and from Hellenism, the dominant culture of his time. This dual conditioning shaped both his thinking and his actions. However, in the First Letter to the Corinthians, we can detect Paul’s distance from the Jewish-Hellenistic identity and the foundational elements of the new theological concepts he shaped on the basis of Christ’s Gospel.
Keywords: body; Duh; Epicureans; epikurejci; freedom; helenizem; Hellenism; Judaism; judovstvo; law (tora, nomos); modrost; odrešenje; postava (tora, nomos); salvation; sistem vedenja (Wissenssystem); slavery; Spirit; stoics; stoiki; suženjstvo; svoboda; system of knowledge (Wissenssystem); telo; wisdom